2021
DOI: 10.3390/molecules26102845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kynurenic Acid on the Rat Aorta Ischemia—Reperfusion Model: Pharmacological Characterization and Proteomic Profiling

Abstract: Kynurenic acid (KYNA) is derived from tryptophan, formed by the kynurenic pathway. KYNA is being widely studied as a biomarker for neurological and cardiovascular diseases, as it is found in ischemic conditions as a protective agent; however, little is known about its effect after ischemia-reperfusion in the vascular system. We induced ischemia for 30 min followed by 5 min reperfusion (I/R) in the rat aorta for KYNA evaluation using functional assays combined with proteomics. KYNA recovered the exacerbated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The activation of ATP synthase potentially overcomes the overall loss of ATP levels, which contributes to cell death upon ischemia. In addition, it has recently been reported that KYNA may enable an enhanced recovery and functionality of an injured ischemic/reperfusion aorta, potentially by promoting reactive oxygen (ROS)- dependent tissue repair via acting on oxidant enzymes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of ATP synthase potentially overcomes the overall loss of ATP levels, which contributes to cell death upon ischemia. In addition, it has recently been reported that KYNA may enable an enhanced recovery and functionality of an injured ischemic/reperfusion aorta, potentially by promoting reactive oxygen (ROS)- dependent tissue repair via acting on oxidant enzymes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed data on the health-promoting effects of KYNA administration in animals regardless of the route of administration are presented in Table S7 [ 26 , 87 , 90 , 93 , 94 , 95 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Kynurenic Acid Supplementationmentioning
confidence: 99%